2021
DOI: 10.1080/15528014.2021.1940688
|View full text |Cite
|
Sign up to set email alerts
|

The joy of foodwork: allergies, gendered foodwork and emotion work in parenting advice, 1991–2020

Abstract: At a time when child health is receiving considerable attention, child feeding practices are under intense scrutiny as the site for developing healthy habits and preventing childhood illness. Previous scholars of foodwork detail the various types of labor involved in feeding children, purchasing foods, researching foods, preparing appealing meals, and managing emotions around these activities. Less scholarly attention has been given to the advice directed at parents -mothers in particular -about feeding childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Her research highlights how racism, neoliberalism and sexism have constrained the efforts of food allergy advocates in trying to create safer spaces for the allergic person. Analysing parenting magazines, Muñoz and Quirke have also emphasised how coping with food allergies is gendered, with mothers expected to do the majority of ‘foodwork’ and ‘emotion work’ related to preventing accidental exposure 78 . Mothers are also more likely to be tasked with liaising with schools and ensuring that a prevention plan is in place 79 .…”
Section: Experiencing Food Allergiesmentioning
confidence: 99%
“…Her research highlights how racism, neoliberalism and sexism have constrained the efforts of food allergy advocates in trying to create safer spaces for the allergic person. Analysing parenting magazines, Muñoz and Quirke have also emphasised how coping with food allergies is gendered, with mothers expected to do the majority of ‘foodwork’ and ‘emotion work’ related to preventing accidental exposure 78 . Mothers are also more likely to be tasked with liaising with schools and ensuring that a prevention plan is in place 79 .…”
Section: Experiencing Food Allergiesmentioning
confidence: 99%
“…Through "good" foodwork, mothers cultivate their identities as mothers, caregivers, and healthy, socially conscious citizens (Cairns & Johnston, 2015;Lupton, 1996;Parker et al, 2019), as well as express care and love for their families, nourish their bodies, and keep them safe MacKendrick, 2018;Muñoz & Quirke, 2021). Mothers must meet nutritional standards set by governing documents like the Dietary Guidelines of Americans while also creating meals that are pleasing and palatable to young mouths (Fielding-Singh, 2021), that diversify and grow children's palates (Wills et al, 2011), and demonstrate conscientiousness by supporting local communities, sustaining ecosystems, and protecting children's safety and "purity" (Cairns et al, 2013;Johnston et al, 2018;Kennedy & Dzialo, 2015;Kennedy & Kmec, 2018;MacKendrick, 2014MacKendrick, , 2018Muñoz & Quirke, 2021). These notions of "good" feeding bear heavily on mothers and rely on the false premise that families'-especially children's-diets derive exclusively from mothers' choices (Backett-Milburn et al, 2010;Beagan et al, 2017;Martens et al, 2004).…”
Section: Foodwork Motherhood and The Gendered Social Organization Of ...mentioning
confidence: 99%
“…Several studies have explored -or mentioned -the influence of class and low income. 12,51,55,64,65,69,70 Minaker et al 55 for example, explored narratives of adults with food allergies who had low incomes as well as 'key' informants -defined as people working in the context of food allergy (e.g. allergists, other health professionals, food bank workers and social assistance employees) in Canada.…”
Section: Low Income Biomedical Bias and Stigmamentioning
confidence: 99%
“…In 2006, DunnGalvin et al 110 published a review article that called for more exploration of gender and food allergy, and some of the consequent psychosocial literature has identified that mothers report poorer quality of life than fathers. 111 The anthropological and sociological research thus far has typically explored food allergy experiences and gender through the context of motherhood, with the focus being primarily on the higher burden on women resulting from gendered dynamics of household labour and childcare in different cultural contexts, 65,67,68,70,90 or on concerns about potential impact on their jobs. 45 Food allergy treatments, such as that of Palforzia and other OIT programmes, have also been shown to put a considerable (gendered) burden on mothers due to the time and skill needed to dose and monitor each day at home.…”
Section: Gender Mothering Advocacy and Emotionsmentioning
confidence: 99%
See 1 more Smart Citation